MODEL KOLABORASI QUADRUPLE HELIX DALAM PENGEMBANGAN WISATA TERPADU DI KECAMATAN LOHIA KABUPATEN MUNA - Usman Rianse; Wa Kuasa Baka; Sitti Hermina; Muhammad Iqbal Kusuma Baka Rianse; Ela Martisa (Journal Publicuho, 2025)
The purpose of this study is to formulate an integrated and effective collaboration model for developing tourist destinations in Lohia District, Muna Regency, to address limited infrastructure, human resource capacity, promotion, tourism product innovation, and low community participation. This research was conducted in Lohia District, Muna Regency. Data collection methods used were observation, in-depth interviews, and literature review. Informants were selected using purposive sampling. The data analysis technique used was descriptive qualitative. The results indicate that: 1) Tourism potential in Lohia District can be developed into marine tourism, agricultural tourism or agrotourism, rural tourism, and cultural tourism; 2) Tourism destination development must be understood holistically and requires collaboration from all parties, including the government, readers, the community, and the media; 4) The quadruple helix collaboration model for integrated tourism development in Lohia District is designed by combining three integrations: 1) Integration of tourism destination development components, 2) Integration of tourism types or themes, and 3) Integration of stakeholders. This approach is called the Triple Quadruple Helix.